An annotated checklist of the chaetonotidan Gastrotricha from India - Chatterjee, Tapas; Todaro, M. Antonio (Zootaxa, 2021)
India has a long history of research on freshwater and marine Gastrotricha. In more than 110 years of study on Order Chaetonotida, two families consisting of 11 genera and 39 species have been described. Thirty of these species are taxa originally described from other continents, while only nine species (7 freshwater, 2 marine) are only known from India. The large percentage (77%) of so-called cosmopolitan species in India has contributed to the phenomenon known as the “meiofauna paradox”. However, a careful review of the pertaining literature provides a different biogeographical picture of the chaetonotidan fauna of India. Herein we show that the high incidence of European and North American species reported from India is mainly due to a mixture of misidentification and species lumping. In fact, for only 12 species there are enough data that would make the Indian specimens morphological similar to taxa previously reported from Europe and/or North America. However, without the appropriate molecular sequence data for comparison, there is no way to rule out the possibility of cryptic speciation.We conclude that further sampling throughout India and the use of more powerful microscopical techniques (e.g., DIC optics) and molecular sequencing will reveal more species and improve the quality of re-descriptions of those (9 spp.) that so far appear to be endemic to the subcontinent. Here we recommend six species to be excluded from the fauna of India while another 11 species (non endemic to India) should be considered dubitatively present in the Indian fauna.